Macromolecules Containing Metal and Metal-Like Elements, Group IVA Polymers - Zeldin Martel (Wiley, 2005)
This series provides a useful, applications-oriented forum for the next generation of macromolecules and materials. Volume 4 provides useful descriptions of Group IV metals and their applications, including silicon-, organogermanium-, organotin-, and organolead-containing polymers. A high-quality team of macromolecular experts from around the world have put together these leading macromolecule titles.